Infant observation and research : emotional processes in everyday lives - Urwin, Cathy; Sternberg, Janine (Hove : Routledge, 2012)
'Psychoanalytic infant observation is frequently used in training psychoanalytic psychotherapists and allied professionals, but increasingly its value as a research method is being recognised, particularly in understanding developmental processes in vulnerable individuals and groups. This book explores how infant observation can be used as a research methodology and discusses the strengths and limitations from a methodological and philosophical point of view.Infant Observation and Research uses detailed case studies to demonstrate the potential of infant observation as a research method. Divided into three sections this book covers:Infant observation as part of the learning processHow infant observation can inform understanding and influence practicePsychoanalytic infant observation and other methodologies.Throughout the book, Cathy Urwin, Janine Sternberg, and their contributors introduce the reader to the nature, scope and value of psychoanalytic infant observation. This book will therefore interest a range of mental health practitioners concerned with early development and infants' emotional relationships, as well as academics and researchers in the social sciences and humanities'--
'Psychoanalytic infant observation is frequently used in training psychoanalytic psychotherapists and allied professionals, but increasingly its value as a research method is being recognised, particularly in understanding developmental processes in vulnerable individuals and groups. This book explores the scope of this approach and discusses its strengths and limitations from a methodological and philosophical point of view. Infant Observation and Research uses detailed case studies to demonstrate the research potential of the infant observation method. Divided into three sections this book covers Infant observation as part of the learning process How infant observation can inform understanding and influence practice Psychoanalytic infant observation and other methodologies. Throughout the book, Cathy Urwin, Janine Sternberg, and their contributors introduce the reader to the nature and value of psychoanalytic infant observation and its range of application. This book will therefore interest a range of mental health practitioners concerned with early development and infants' emotional relationships, as well as academics and researchers in the social sciences and humanities'--
Includes bibliographical references and index.
Keywords: Infant psychology; Psychoanalysis